Artificial intelligence boosting food safety immunoassays: technological advances and applications - Ming-Xi He; Ri-Sheng Chen; Dong Huang; Zhen-Lin Xu; Aori Qileng (Current Opinion in Food Science, 2026)

Impact of Cultivation on Soil Phosphorus Content along the Altitude Gradient in Alpine Forest of the Tibetan Plateau - Yuxuan Cui; Xu-Ri; Fengzi Li; Songbo Qu; Ribu Shama; Lin Zhang; Eryuan Liang (Journal of Soil Science and Plant Nutrition, 2026)

An integrated multi-omics approach for deciphering podophyllotoxin-induced nephrotoxicity via the microbiome-gut-kidney (MGK) axis based on the toxicological evidence (TEC) concept - Xiaole Guo; Yu Wang; Lei Wang; Yan Lei; Ri-na Sa; Lili Li; Shengnan Xia; Xiaoming Lin; Chuanxin Liu; Yuanyang Shao (Journal of Molecular Histology, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Novel hapten design and highly sensitive monoclonal antibody–based immunochromatographic assay for benzo[a]pyrene in edible oil - Huan-Yuan Xu; Ri-Sheng Chen; Yu Wang; Yue-ming Chen; Sumed Yadoung; Surat Hongsibsong; Peiqiang Shuai; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2026)

Associations of air pollution and genetic risk and their interaction with risk of Alzheimer’s disease: identification of risk loci and potential biological pathways - Shanshan Ran; Jingyi Zhang; Miao Cai; Lan Chen; Zhengmin Qian; Fei Tian; Gan Wu; Ri’enna Boyd; Stephen Edward McMillin; Huai-cai Zeng; Yin Yang; Hualiang Lin (GeroScience, 2026)

The glutamyl-prolyl-tRNA synthetase 1 inhibitor halofuginone exerts synergistic antitumor effects with bortezomib in colon cancer cells - Han Lin; Ying Yan; Chenyu Qiu; Junqi Wang; Wenying Fu; Chongchong Shu; Yinghua Chen; Chenxin Xu; Shaotang Li; Yiqun Xia; Jundixia Chen; Yunzhi Chen; et al. (Toxicology and Applied Pharmacology, 2026)

Machine learning-assisted sensor array based on enhanced dual enzyme-like activities of Fe SAzymes modulated via Pluronic surfactant for multi-category perfluoroalkyl intelligent recognition and quantification - Wen-Cai Jiang; Xiao-Mei Li; Jia-Hao Cheng; Li-Yao Xu; Ri-Za He; Gui-Lin Zou; Zhi-Bo Hou; Yan Zhao; Guo-Qi Zhang (Chemical Engineering Journal, 2026)

Machine learning intelligently selects feature values to construct a sensor array based on tri-functional Mn-doped covalent organic polymer nanozymes for identifying flavonoid compounds - Guo-Qi Zhang; Wen-Cai Jiang; Xiao-Mei Li; Ren-Jie Li; Yi Feng; Ri-Ge Li Nai; Hui-Lin Cheng; Zhi-Bo Hou; Xiao-Jun Luo; Yan Zhao (Food Chemistry, 2025)

Rapid and efficient stem segment regeneration propagation system for Euonymus bungeanus - Kai-Ge Cui; Hao-Lin Wang; Wen-Yue Quan; Zhuo-Zhuo Ye; Cheng-Ri Zhao (South African Journal of Botany, 2025)

2-Arylbenzofurans from the stems and leaves of Artocarpus tonkinensis and their potential antiproliferative activities - Jia-Ming Guo; Lin-Xuan Li; Xin-Yi Li; Tian-Yu Wang; En-Ning Zhu; An-Jiao Wu; Shu-Ri Li; Hui- Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2025)

Demethoxycurcumin induces metabolic crisis and ATF4/ATF3/CHOP-dependent cell death in hepatocellular carcinoma - Fugen Shangguan; Hongfei Zhou; Huachang Zhang; Thaiyuri Reddy; Mhaka Panashe Bryan; Ri Cui; Jianhu Lin; Yongping Chen; Yihu Zheng (Chemico-Biological Interactions, 2025)

Effects of cultivation on soil carbon and nitrogen along an altitudinal gradient in the Southeastern Tibetan Plateau - Haojing Lei; Fengzi Li; Xu-Ri; Songbo QU; Ribu Shama; Lin Zhang; Eryuan Liang (Forest Ecology and Management, 2025)

Chlorinated paraffins exposure in particulate matter increase the risk of attention-deficit/hyperactivity disorder symptoms in children and adolescents - Wan-Ting He; Jing-Wen Huang; Yun-Ting Zhang; Edwin Trevathan; Zhengmin Qian; Ri'enna Boyd; Michael Elliott; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Guang-Hui Dong (Environmental Pollution, 2025)

Field study on uplift bearing capacity of pre-bored grouted planted pile and bored pile in deep soft soil - Jia-jin Zhou; Ri-hong Zhang; Xiao-nan Gong; Jian-lin Yu (Ocean Engineering, 2025)

Adaptive reward shaping based reinforcement learning for docking control of autonomous underwater vehicles - Shuguang Chu; Mingwei Lin; Dejun Li; Ri Lin; Sa Xiao (Ocean Engineering, 2025)

Soil properties, climate, and topography jointly determine plant community characteristics in marsh wetlands - Lin Yuan; Jingzhi Wang; Rong Liu; Yuqi Tang; Di Wu; Ri Jin; Weihong Zhu (Journal of Plant Research, 2025)

Effects of alligator weed invasion on wetlands in protected areas: A case study of Lishui Jiulong National Wetland Park - Xiang-Hua Fang; Xuan-Ming Chen; Ri-Lin Liu; Si-Hai Zhang; Jun-Qin Gao; Bi-Cheng Dong; Fei-Hai Yu (Science of The Total Environment, 2024)

Frequency optimization of the AUV wireless charging system for minimum energy dissipation - Ri Lin; Mingwei Lin; Canjun Yang; Dejun Li; Zhuoyu Zhang (Ocean Engineering, 2024)

Monoclonal antibody based colloidal gold immunochromatographic assay for the visual and rapid screening of profenofos - Ri-Sheng Chen; Jian-Cheng Yuan; Chong-Lan Luo; Yu Wang; Zi-Jian Chen; Ze-Shan Lin; Zhen-Lin Xu (Environmental Pollution, 2024)

Static Model of the Underwater Soft Bending Actuator Based on the Elliptic Integral Function - Ri Lin; Anzhe Yi; Mingwei Lin; Canjun Yang; Zhuoyu Zhang (Journal of Marine Science and Engineering, 2024)
Underwater soft manipulators are increasingly used for grasping underwater organisms and cultural relics due to their compliance and ability to protect delicate objects. Unlike rigid manipulators, these soft manipulators feature underwater soft bending actuators that deform under external forces, making their shape and output force challenging to predict. Consequently, classical beam theory is no longer applicable. To address these issues, this article models the underwater soft bending actuator as a cantilever beam and establishes its shape and output force using elliptic integral functions. Additionally, this article proposes a method for determining the unknown parameters of the driver shape and output force model using optimization techniques and introduces a solution process based on the particle swarm optimization framework. Given the role of tensile and bending stiffness in the actuator’s performance, this paper employs a parameter identification method based on length and bending angle information. Tests demonstrate that the proposed method effectively estimates the deformation and output force of the underwater soft bending actuators, confirming its accuracy.

Underwater fluid-driven soft dock for dynamic recovery of AUVs with improved pose tolerance - Mingwei Lin; Anzhe Yi; Ri Lin; Xin Wu; Bohao He; Bolun Zhang; Canjun Yang (Ocean Engineering, 2024)

Gaze-Assisted Prescribed Performance Controller for AUV Trajectory Tracking in Time-Varying Currents - Zhuoyu Zhang; Mingwei Lin; Dejun Li; Ri Lin (Journal of Marine Science and Engineering, 2024)
Trajectory tracking for underactuated autonomous underwater vehicles (AUVs) is challenging due to coupling dynamics, modeling inaccuracies, and unknown disturbances. To tackle this, we propose a decoupling gaze-assisted prescribed performance controller (GAPPC). We first use an error transformation approach to achieve the prescribed performance, incorporating the line-of-sight (LOS) algorithm and an event-triggering mechanism to handle the kinematic characteristics of underactuated AUVs. Next, we develop a control strategy for the transformed error that does not require knowledge of the model parameters, including fast dynamic compensation to reduce steady-state errors. Finally, we analyze the controller’s stability and present simulation results. Simulations, which account for modeling inaccuracies and unknown ocean currents, show that the GAPPC improves stability errors by 67.3% compared to the adaptive robust controller.

Di-(2-ethylhexyl) phthalate and its metabolites research trend: a bibliometric analysis - Hyonju Ri; Ying Zhu; Hyonsu Jo; Xiaohan Miao; Unsim Ri; Jianli Yin; Liting Zhou; Lin Ye (Environmental Science and Pollution Research, 2024)

Surface charge accumulation of functionalized carbonized polymer dots selectively induces lysosomal membrane permeabilization of breast cancer cells - Yu Lei; Bao-Hua Tian; Xin-Xin Li; Ming-Yuan Sun; Xi-Lin Guo; Yi-Da Wang; Hui-Qing Zhou; Ri-Sheng Ma; Hai-Xia Liang (Chemical Engineering Journal, 2024)

Image stitching and target perception for Autonomous Underwater Vehicle-collected side-scan sonar images - Zhuoyu Zhang; Rundong Wu; Dejun Li; Mingwei Lin; Sa Xiao; Ri Lin (Frontiers in Marine Science, 2024)
Introduction Autonomous Underwater Vehicles (AUVs) are capable of independently performing underwater navigation tasks, with side-scan sonar being a primary tool for underwater detection. The integration of these two technologies enables autonomous monitoring of the marine environment. Methods To address the limitations of existing seabed detection methods, such as insufficient robustness and high complexity, this study proposes a comprehensive seabed detection method based on a sliding window technique. Additionally, this study introduces a sonar image stitching method that accounts for variations in image intensity and addresses challenges arising from multi-frame overlaps and gaps. Furthermore, an autonomous target perception framework based on shadow region segmentation is proposed, which not only identifies targets in side-scan sonar images but also provides target height measurements. Results Comprehensive seabed detection method improves accuracy by 31.2% compared to the peak detection method. In experiments, the height measurement error for this method was found to be 9%. Discussion To validate the effectiveness of the proposed seabed detection method, sonar image stitching method, and target perception framework, comprehensive experiments were conducted in the Qingjiang area of Hubei Province. The results obtained from the lake environment demonstrated the effectiveness of the proposed methods.

Autonomous Underwater Vehicle Cruise Positioning and Docking Guidance Scheme - Zhuoyu Zhang; Wangjie Ding; Rundong Wu; Mingwei Lin; Dejun Li; Ri Lin (Journal of Marine Science and Engineering, 2024)
The Autonomous Underwater Vehicle (AUV) is capable of autonomously conducting underwater cruising tasks. When combined with docking operations, the AUV can replenish its electric power after long-distance travel, enabling it to achieve long-range autonomous monitoring. This paper proposes a positioning method for the cruising and docking stages of AUVs. Firstly, a vision guidance algorithm based on monocular vision and threshold segmentation is studied to address the issue of regional noise that commonly occurs during underwater docking. A solution for regional noise based on threshold segmentation and proportional circle selection is proposed. Secondly, in order to enhance the positioning accuracy during the cruising stage, a fusion positioning algorithm based on particle filtering is presented, incorporating the Doppler Velocity Log (DVL) and GPS carried by the AUV. In simulation, this algorithm improves positioning accuracy by over 56.0% compared to using individual sensors alone. Finally, experiments for cruising and docking were conducted in Qingjiang, Hubei, China. The effectiveness of both methods is demonstrated, with successful docking achieved in four out of five attempts.

Debris flow susceptibility assessment based on boosting ensemble learning techniques: a case study in the Tumen River basin, China - Zelu Chen; Hechun Quan; Ri Jin; Zhehao Lin; Guangzhu Jin (Stochastic Environmental Research and Risk Assessment, 2024)

Gold nanocluster-based ratiometric fluorescence immunoassay for broad-spectrum screening of five eugenols - Lin Luo; Zhen-Xi He; Bao-Zhu Jia; Rui-Yao Kang; Wen-Feng Zhang; Ri-Ming Huang; Zhen-Lin Xu (Analytica Chimica Acta, 2024)

CRISPR/Cas9-mediated knockout of Bsr-d1 enhances the blast resistance of rice in Northeast China - Ying Zhang; Xiu-Feng Lin; Li Li; Ri-Hua Piao; Songquan Wu; Anqi Song; Mengmeng Gao; Yong-Mei Jin (Plant Cell Reports, 2024)

Chemical constituents from the stem of Ficus pumila - Wen-Lin Xiao; Wen-Hao Chen; Wei Li; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2024)

Lignan glucosides from Gentiana macrophylla with potential anti-arthritis and hepatoprotective activities - Pei-Qi Huang; Kai-Wen Kang; Dan-Yu Huang; Chun-Lin Zhao; Hao Zheng; Yong-Xin Luo; Yan Wen; Ming-Feng Zou; Dong-Li Li; Ri-Hui Wu; Yun-Cai Tian; Yong Tian; et al. (Phytochemistry, 2024)

Development of a Radially Coupled Wireless Charging System for Torpedo-Shaped Autonomous Underwater Vehicles - Mingwei Lin; Ri Lin; Dejun Li; Runtian Duan (Journal of Marine Science and Engineering, 2023)
Spiral coaxial coils are widely used in wireless charging systems for autonomous underwater vehicles (AUVs). However, these coils can generate axial electromagnetic interference that may adversely affect the electronic components contained within the AUV. In order to overcome this issue, this paper introduced a pair of radially coupled coils which implement distributed ferrite cores. The mathematical model of the curly coils was derived, and its geometry parameters were optimized through the use of genetic algorithms. ANSYS Maxwell was used to analyze and optimize the layout of the ferrite cores. A prototype of the AUV wireless charging system was presented, demonstrating a maximum efficiency of 94% at 2.2 kW in salt water. The rotation adaptivity of the system was also tested, revealing stable output performance within the possible roll-angle variations of the AUV.

Underwater Electromagnetic Guidance Based on the Magnetic Dipole Model Applied in AUV Terminal Docking - Ri Lin; Yucheng Zhao; Dejun Li; Mingwei Lin; Canjun Yang (Journal of Marine Science and Engineering, 2022)
To address the poor effect of optical/visual guidance used in AUV terminal docking with strong background light and turbid water quality, an underwater electromagnetic guidance method based on the magnetic dipole model is proposed in this paper. According to the magnetic dipole model, the electromagnetic field of 1 kHz frequency generated by the coil in the range of terminal docking is the near field, where the position can be figured out through the amplitude and phase information of three orthogonal magnetic field intensity vectors. A triaxial-coil magnetometer with three orthogonal coils and a method for extracting the amplitude and phase information of the induced voltage are presented in this paper. According to Faraday’s law, the amplitude and phase information of the induced voltage of a triaxial-coil magnetometer replace the information of magnetic field intensity in relation to positioning. The underwater positioning results show that the average positioning error within 6 m can reach the centimeter level. Five underwater terminal docking tasks were carried out, and four of them were successfully completed, which verified the feasibility of the proposed method.

Production and Evaluation of a Novel Multi-Epitope Bivalent Vaccine Against Echinococcus multilocaularis Metacestode - Runle Li; Mingyuan Xin; Kunmei Liu; Bingwen Hu; Jingwei Ma; Pei Zhou; Lin Feng; Mingquan Pang; Ri-li Ge; Haining Fan; Le Guo; Feng Tang (International Journal of Peptide Research and Therapeutics, 2022)

Two new cephalochromin derivative from the Alternaria sp. ZG22 - Xin-Ming Song; Xue-Ming Zhou; Ya-Ling Li; Li-Bing Huang; Cai-Cui Chen; Yan Gao; Lin He; Xiao-qun Mao; Bing Chen; Jing-Wen Liu; Hui-Jie Liu; Xiao-Ping Song; et al. (Natural Product Research, 2021)

Dendrocoumarin: a new benzocoumarin derivative from the stem of Dendrobium nobile - Xue-Ming Zhou; Bin Zhang; Guang-Ying Chen; Chang-Ri Han; Kun-Chi Jiang; Ming-Yue Luo; Bo-Zheng Meng; Wen-Xin Li; Shi-Dai Lin (Natural Product Research, 2018)

Chemical composition of Illicium verum fruit extract and its bioactivity against the peach–potato aphid, Myzus persicae (Sulzer) - Shi-Guang Li; Ben-Guo Zhou; Mao-Ye Li; Su Liu; Ri-Mao Hua; Hua-Feng Lin (Arthropod-Plant Interactions, 2017)

An Experimental and Numerical Study on Mechanical Behavior of Ubiquitous-Joint Brittle Rock-Like Specimens Under Uniaxial Compression - Ri-hong Cao; Ping Cao; Xiang Fan; Xinguang Xiong; Hang Lin (Rock Mechanics and Rock Engineering, 2016)

Increasing the immune activity of exosomes: the effect of miRNA-depleted exosome proteins on activating dendritic cell/cytokine-induced killer cells against pancreatic cancer - Ri-sheng Que; Cheng Lin; Guo-ping Ding; Zheng-rong Wu; Li-ping Cao (Journal of Zhejiang University-SCIENCE B, 2016)

Mechanical Behavior of Brittle Rock-Like Specimens with Pre-existing Fissures Under Uniaxial Loading: Experimental Studies and Particle Mechanics Approach - Ri-hong Cao; Ping Cao; Hang Lin; Cheng-zhi Pu; Ke Ou (Rock Mechanics and Rock Engineering, 2016)

Isolation, diversity and acetylcholinesterase inhibitory activity of the culturable endophytic fungi harboured in Huperzia serrata from Jinggang Mountain, China - Ya Wang; Zheng Lai; Xi-Xi Li; Ri-Ming Yan; Zhi-Bin Zhang; Hui-Lin Yang; Du Zhu (World Journal of Microbiology and Biotechnology, 2016)

Circulation and in vivo distribution of duck hepatitis A virus types 1 and 3 in infected ducklings - Shao-Li Lin; Ri-Chao Cong; Rui-Hua Zhang; Jun-Hao Chen; Lin-Lin Xia; Zhi-Jing Xie; Yu Wang; Yan-Li Zhu; Shi-Jin Jiang (Archives of Virology, 2016)

Fumigant activity of Illicium verum fruit extracts and their effects on the acetylcholinesterase and glutathione S-transferase activities in adult Sitophilus zeamais - Shi-Guang Li; Mao-Ye Li; Yan-Zhang Huang; Ri-Mao Hua; Hua-Feng Lin; Yu-Jie He; Lin-Lin Wei; Zhu-Qin Liu (Journal of Pest Science, 2013)

Erratum to: AtCPK6, a functionally redundant and positive regulator involved in salt/drought stress tolerance in Arabidopsis - Jing Xu; Yong-Sheng Tian; Ri-He Peng; Ai-Sheng Xiong; Bo Zhu; Xiao-Fen Jin; Feng Gao; Xiao-Yan Fu; Xi-Lin Hou; Quan-Hong Yao (Planta, 2010)

AtCPK6, a functionally redundant and positive regulator involved in salt/drought stress tolerance in Arabidopsis - Jing Xu; Yong-Sheng Tian; Ri-He Peng; Ai-Sheng Xiong; Bo Zhu; Xiao-Fen Jin; Feng Gao; Xiao-Yan Fu; Xi-Lin Hou; Quan-Hong Yao (Planta, 2010)

Cyanobacteria MT gene SmtA enhance zinc tolerance in Arabidopsis - Jing Xu; Yong-Sheng Tian; Ri-He Peng; Ai-Sheng Xiong; Bo Zhu; Xi-Lin Hou; Quan-Hong Yao (Molecular Biology Reports, 2010)

Isolated and characterization of a cDNA encoding ethylene-responsive element binding protein (EREBP)/AP2-type protein, RCBF2, in Oryza sativa L. - Jin-Ge Liu; Zhen Zhang; Qiu-Lin Qin; Ri-He Peng; Ai-Sheng Xiong; Jian-Min Chen; Fang Xu; Hong Zhu; Quan-Hong Yao (Biotechnology Letters, 2006)

Spatial-temporal changes and trends of ageing in China - Wu-yi Wang; Li Zhang; Hai-rong Li; Ri-bang Li; Lin-sheng Yang; Yong-feng Liao (Chinese Geographical Science, 2005)